Metastatic Lung Cancer: Emerging Therapeutic Strategies - Saif Ur Rehman, Sana; Ramalingam, Suresh S. (Seminars in Respiratory and Critical Care Medicine, 2016)
Advanced stage nonsmall cell lung cancer had been treated mainly with platinum-based doublet chemotherapy, and other cytotoxic agents that offered significant survival advantage over best supportive care, until recently. Modest improvements were achieved with the addition of antibodies targeting the vascular endothelial growth factor, and the introduction of maintenance chemotherapy. Improvements in our knowledge of lung cancer biology have shifted the current treatment paradigm from being based on histology to one based on molecular biomarkers. Identification of potentially targetable driver mutations in a subgroup of these patients, pertaining to genes directing cell signaling pathways involved in proliferation and survival, has been the single most influential development in the treatment of lung cancer in the last two decades. Personalized medicine based on driver mutations offers enhanced efficacy at the expense of relatively minimal toxicity burden. Targeting the epidermal growth factor receptor pathway in patients with an activating mutation results in substantial improvement in patient outcome. Similarly, targeting ALK (anaplastic lymphoma kinase) fusion gene with first- and second-generation inhibitors results in improved efficacy over chemotherapy. For certain other mutations such as MET exon 14 and BRAF, promising inhibitory strategies are being investigated. In addition, the recent emergence of immune checkpoint inhibitors to reverse exhaustion of T cells has been a major breakthrough in rapidly changing the therapeutic landscape for lung cancer. This article reviews the role of systemic therapy in advanced stage lung cancer.
Keywords: lung cancer; NSCLC; metastatic; chemotherapy; targeted therapy; EGFR; anaplastic lymphoma kinase